Heat transfer within frozen slopes in subarctic Yukon, Canada. Issue 6 (4th May 2016) - Steeves, Joel T; Barbour, Sidney Lee; Ferguson, Grant; Carey, Sean K
Abstract : The dominant mechanism of heat transfer during ground thaw is typically assumed to be vertical conduction. However, the addition of lateral subsurface water flow introduces the potential for the forced convection of energy, having an influence on ground temperatures and thaw rates. Field observations of snowmelt run-off and rates of ground thaw for two slopes within the Wolf Creek basin, Yukon, Canada, highlighted different rates of ground thaw with slope position. Ground temperatures were numerically simulated to evaluate the relative influence of conduction and convection on the thawing of these slopes; each slope comprised different soils and had a different slope aspect. Both slopes were composed of an organic layer overlying a mineral soil. Lateral water flow above the frozen layer occurred within both slopes as a result of a perched saturated zone above the organic–mineral interface. The numerical models reveal that lateral diversion within a surficial, high-hydraulic conductivity layer, such as an organic layer, can initiate convective heat transfer. However, the observed differential thaw was determined to be a result of conduction and variations in the initial ice content and snow cover rather than lateral convection of heat.